A validation study of the Stoyanova et al. method (2017) for age-at-death estimation quantifying the 3D pubic symphyseal surface of adult males of European populations - Kotěrová, Anežka; Velemínská, Jana; Cunha, Eugénia; Brůžek, Jaroslav (International journal of legal medicine, 2019)
The age-at-death estimation thresholds have recently been shifted towards a more objective assessment of the aging process. Such a non-subjective approach offers quantitative methods of age estimation; for instance, the method relating to the surfaces of pubic symphyses of males published by Stoyanova et al. (J Forensic Sci 62:1434-1444, 2017). A validation study was conducted to test the method performance in European samples. The sample consisted of 96 meshes of pubic symphyses of male individuals (known sex and age) that came from four different samples (two Portuguese collections, one Swiss, and one Crete). Stoyanova's method based on five regression models (three univariate and two multivariate models) performed worse in our sample, but only when the whole sample (without age limitation) was included. A sample limited to individuals under 40 years of age achieved better results in our study. The best results were reached through the thin plate spline algorithm (TPS/BE) with a root mean square error of 5.93 years and inaccuracy of 4.47 years. Generally, the multivariate regression models did not contribute to better age estimation. In our sample in all age categories, age was systematically underestimated. The quantitative method tested in this study works best for individuals under 40 years of age and provides a suitable basis for further research.
Keywords: Forensic Anthropology; Imaging, Three-Dimensional; Quantitative analysis; soudní antropologie; Humans; Structured light scanning; lidé středního věku; 3D model; Evropa; Computer Simulation; Aged; mladý dospělý; dospělí; Pubic symphysis; určení kostního věku; senioři; lidé; Age-at-death; Europe; Regression Analysis; Adult; počítačová simulace; Male; Middle Aged; Age Determination by Skeleton; Aged, 80 and over; Young Adult; senioři nad 80 let; zobrazování trojrozměrné; mužské pohlaví; symphysis pubica; Pubic Symphysis; regresní analýza